STRATEGI PEMBELAJARAN DIFERENSIASI DALAM PENDIDIKAN AGAMA ISLAM UNTUK MENGAKOMODASI KERAGAMAN KEBUTUHAN BELAJAR PESERTA DIDIK - Abdul Rahman, Nur Amalina; Rosmiati Ramli; Adyana, Nurul Ilmi; Rekha, Jeny (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
The diversity of students’ characteristics in Islamic Religious Education (PAI) learning requires instructional strategies that are able to accommodate differences in students’ abilities, interests, and learning styles. In practice, PAI learning is often implemented using uniform approaches that have not fully addressed the diverse learning needs of students. This study aims to analyze differentiated learning strategies in Islamic Religious Education as an effort to accommodate the diversity of students’ learning needs. This research employs a qualitative approach using a literature study method by examining various academic sources such as scientific journals, books, and other scholarly publications related to differentiated instruction and Islamic education. Data were analyzed through the processes of data reduction, data presentation, and thematic conclusion drawing. The findings indicate that differentiated learning strategies in PAI can be implemented through four main aspects: content differentiation, process differentiation, product differentiation, and learning environment differentiation. The application of these strategies enables teachers to adjust learning materials, instructional methods, learning activities, and assessment forms according to students’ characteristics and learning needs. Therefore, differentiated instruction has positive implications for improving students’ engagement, understanding, and learning experiences in Islamic Religious Education, making the learning process more inclusive, adaptive, and effective.